KUALITAS AIR TANAH DANGKAL DI KENAGARIAN ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Syefrina, Syefrina; Dasrizal, Dasrizal; Farida, Farida (STKIP PGRI Sumbar, 2013)
This research has purpose to get data about how condition physical of shallow ground water. The result of processing of data, explain that the quality of shallow ground water physically in Kenagarian Alahan Panjang based in temperature of water about 20,0ÂºC-24,5ÂºC, temperature of water is too low. Shallow ground water at Jorong Usak is pale brown, smell ground and terteless. At Jorong Alahan Panjang is brown, saur taste. At Jorong Taluak Dalam is pure Taratak Galundi is pure. no smell and like ground. so Jorong Taluak Dalam and Taratak Galundi fill requirement quality of water physically. but Jorong Usak and Alahan Panjang do not fill requirement quality of drink water physically because have calour, smell and taste. Based on condition of water in chemisÂ try, shallow groundâs water is pH about 6.11-7.12 mg/l. Fe in sample about 0.000-0.075 mg/l. Mangan about 0.000-0.041 mg/l and hardness about 12.7405-124.0705 mg/l. So based on result of researah in laboratory the quality of shallow/ground water in Kenagarian Alahan Panjang fill standard from MenKes but from the chemistryâs parameter of Kesadahan is too high so that it is not suitable with standard from MenKes. Based on condition of biology bactery that incdude in shallow ground water about 0-13 ecoli/100 sample. So from result of research in laboratory just Jorong Usak that fill standard quality of drink water but Jorong Alahan Panjang, Taluak Dalam and Taratak Galundi are not suitable with standard quality of drinking water.Â